The CGIAR-R4D on Climate Change in Vietnam and Southeast Asia (Conference Highlights) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
To exchange learnings in strengthening the research for development (R4D) on climate change towards achieving a climate-resilient Southeast Asia (SEA), the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS SEA), in cooperation with the ASEAN Climate Resilience Network (ASEAN CRN), GIZ, and the Ministry of Agriculture and Rural Development of Vietnam, organized the conference, “The CGIAR-R4D on Climate Change in Vietnam and Southeast Asia.” Held 28 November 2018 at the Melia Hotel in Hanoi, the conference convened key stakeholders to discuss the role of R4D in combatting the threats of climate change and to explore areas of collaboration among countries and other relevant actors to achieve climate resilience in the region.